Coordinated batch processing machine scheduling with job delivery in semiconductor manufacturing - Fu, Qing. (2013)
In the make-to-order (MTO) business model, manufacturing and outbound transportation are intimately linked due to little or no finished product inventory. Collaborative planning of the production and delivery is desired. This research seeks to explore a new collaborative scheduling method for production and distribution in supply chain for discrete manufacturing and distribution environment. A coordinated production and delivery scheduling problem, in which jobs are processed on a single batch processing machine (BPM) and then delivered to geographically dispersed customers, is addressed. The coordinated production and distribution model is applicable in many industries such as the integrated circuit (IC) burn-in process and delivery in the subcontract semiconductor assembly and test environment. Burn-in operation is operated in burn-in processor, which is considered as a type of batch processing machine in the semiconductor manufacturing. IC products after the burn-in operation are shipped to customers in different locations for the final test.